An activist handbook for the education revolution : United Opt Out's test of courage - McDermott McNulty, Morna; Robertson, Peggy; Jensen, Rosemarie; Smith, Ceresta (Emerald Publishing Limited : Information Age Publishing Inc., 2015)
This book is intended for educators, parents and community activists interested in reclaiming our public schools and reclaiming the public narrative around education policy. The book infuses research about the recent history of education policy reform, the strategies United Opt Out uses for fighting back against these policies, and proposes solutions that work to create sustainable, equitable, anti-racist, democratic and meaningful public education. This book is for anyone interested in an "insider's look" behind the scene of forming an organization, or leading a resistance. Simultaneously the book provides scholarly-based research about the broader issues, policies and data around education reform, and the opt out movement.Education policy has been heating up ever since NCLB but especially since the roll out of Race to The Top and the Common Core State Standards. Nationally publicized debates and discord over these policies are garnering public attention of teachers, parents, and whole communities. We hope this book will add to the library of other recent books such as Mercedes Schneider's A Chronicle of Echoes (2014), Diane Ravitch's Reign of Error (2013) and Bowers & Thomas (eds) Detesting and Degrading Schools (2012), that have exposed the complex corporate interest in shaping education policies and the destructive influence such policies will have on our children and on our democracy. This book uses first person narratives infused with research and scholarship, to create personalized accounts into the life of education activism. Each chapter includes an Activists Handbook section to provide support for our activist/readers in their own efforts. We hope that our experiences will inspire others to take this charge upon themselves as well.